Organic self-charging flow battery based on quinone molecules and preparation method thereof
By using 蒽醌 -2,7-sodium diulfonate as a combination of cricket-2,7-sodium diulfonate as a combination of positive poles, zinc, aluminum, or magnesium, the energy density density density of zinc-based liquid flow battery is low and limited battery capacity The problem realizes high energy density and self -charging function, and improves the cycle stability and cost benefits of the battery.
Patent Information
- Application Number
- CN202411494383.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In actual applications, existing zinc-based flow batteries have problems such as low energy density, limited battery capacity, and low power density and reliability.
The organic self-self-charging liquid battery based on the molecular molecules is used, and the 蒽醌 -2,7-sodium diulfate is used as the positive electrode material, combined with zinc, aluminum, or magnesium as a negative electrode material, and the battery voltage is adjusted through acidic conditions to achieve electrochemical reversible reversal Sexual and self -charging function.
The energy density and battery capacity of the battery is improved, and the long -term cycle and capacity maintenance rate have been achieved. The battery capacity is increased through the chemical self -charging process, reducing costs.
Smart Images

Figure CN119381487A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery preparation, and in particular to an organic self-charging liquid flow battery based on quinone molecules and a preparation method thereof. Background Art
[0002] As global fossil energy consumption brings environmental problems to mankind, the demand for renewable energy is growing rapidly. The electricity generated by renewable energy is unstable and intermittent, which is a major obstacle to its widespread application. Energy storage technology, especially flow battery technology, is a safe and effective way to solve this problem. At present, flow batteries can be divided into traditional flow batteries such as vanadium flow batteries, zinc-based flow batteries, iron-chromium flow batteries, and new flow battery systems such as organic flow batteries, which have great prospects in energy storage applications. Among the above-mentioned flow batteries, zinc-based flow batteries that utilize the plating-stripping process of the negative zinc redox couple have good application prospects in distributed energy storage due to their attractive characteristics such as high safety, high energy density and low cost. Compared with the energy density of vanadium flow batteries (25-35Wh / L) and iron-chromium flow batteries (10-20Wh / L), the energy density of zinc-bromine flow batteries (40-90Wh / L) and zinc-iodine flow batteries (-167Wh / L) is much higher due to the high solubility of halide ions and high battery voltage. However, their disadvantages are small valence charge, limited electron transfer capacity, strong corrosiveness, and the need to work in corrosive electrolyte solutions such as concentrated sulfuric acid. Although vanadium redox flow batteries (RFBs) have been commercialized, the scarcity of vanadium makes such batteries expensive, and its toxicity raises safety concerns. Zinc-based flow battery technology is considered a promising distributed energy storage solution. However, their upgrading in practical applications still faces challenges, such as the limited area capacity of dendrite zinc and negative electrode, relatively low power density and reliability.
[0003] Aqueous aluminum batteries are a post-lithium battery technology for large-scale energy storage applications due to their abundant raw materials, low cost, high safety, and high theoretical capacity. However, their development has been hampered by the unsatisfactory electrochemical behavior of aluminum metal electrodes due to the presence of an oxide layer and hydrogen side reactions.
[0004] Redox-active organic and organometallic molecules have been extensively studied for their promise in developing inexpensive flow batteries. These molecules exhibit structural diversity and extensive tunability, allowing for the engineering of solubility, redox potential, kinetics, and stability. Many different types of molecules, including quinones, phenazines, viologens, alloxazines, and (2,2,6,6-tetramethylpiperidin-1-yl)oxygenates, have demonstrated promising redox-active materials in aqueous organic redox flow batteries (AORFBs).
[0005] Most of these molecules exhibit low reduction potentials and have therefore been explored as negative electrolyte materials. Exceptions are tetrachloro-1,4-benzoquinone and 4,5-dihydroxybenzene-1,3-disulfonic acid, which have high positive reduction potentials >0.8 V versus the Standard Hydrogen Electrode (SHE) in acidic solutions. Therefore, by combining these high potential organic molecules with Zn / [Zn(OH)4] 2- By pairing redox couples, a new type of hybrid RFB can be designed to achieve high battery voltage. + or OH - Cross-talk, it is difficult to pair alkaline electrolytes and acidic electrolytes in conventional single-membrane RFBs. In recent years, ceramic membranes and bipolar polymer membranes have been introduced into single-membrane pH-difference flow batteries, but the high resistance of these membranes severely limits the current density. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides an organic self-charging liquid flow battery based on quinone molecules and a preparation method thereof. The anthraquinone derivatives used in the organic self-charging liquid flow battery based on quinone molecules provided by the present invention have excellent electrochemical reversibility, which effectively solves the problems of low energy density and limited battery capacity of traditional zinc-organic liquid flow batteries.
[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention to solve its technical problems is: to provide an organic self-charging liquid flow battery based on quinone molecules, the positive electrode electrolyte of the organic self-charging liquid flow battery based on quinone molecules includes sodium anthraquinone-2,7-disulfonate, inorganic salt, ammonium chloride and sulfuric acid, and the negative electrode electrolyte of the organic self-charging liquid flow battery based on quinone molecules includes inorganic salt, ammonium chloride and sulfuric acid.
[0008] Furthermore, the inorganic salt in the positive electrode electrolyte and the inorganic salt in the negative electrode electrolyte are both one of zinc trifluoromethanesulfonate, magnesium sulfate and aluminum chloride.
[0009] The method for preparing the above-mentioned organic self-charging liquid flow battery based on quinone molecules comprises the following steps:
[0010] S1. Add sodium anthraquinone-2,7-disulfonate, inorganic salt, ammonium chloride and sulfuric acid into deionized water and stir evenly, then perform ultrasonic treatment, and then perform ventilation bubbling treatment to obtain a positive electrode electrolyte;
[0011] S2, adding inorganic salt, ammonium chloride and sulfuric acid into deionized water, stirring evenly, and then performing ultrasonic treatment to obtain a negative electrode electrolyte;
[0012] S3, cutting the ion membrane and then activating it through pretreatment;
[0013] S4. Ultrasound the components of the battery, and then assemble them in sequence. Then, the positive and negative electrodes are separated by an ion membrane. The positive electrode electrolyte obtained in step S1 and the negative electrode electrolyte obtained in step S2 are pumped into the battery by a peristaltic pump. Then, a resistance test is performed to obtain an organic self-charging liquid flow battery based on quinone molecules.
[0014] Furthermore, in step S1, the volume of the positive electrode electrolyte is 5-15 mL.
[0015] Furthermore, in step S1, the volume of the positive electrode electrolyte is 10 mL.
[0016] Furthermore, in step S1, the concentration of sodium anthraquinone-2,7-disulfonate in the positive electrode electrolyte is 0.05-0.15 mol / L.
[0017] Furthermore, in step S1, the concentration of sodium anthraquinone-2,7-disulfonate in the positive electrode electrolyte is 0.1 mol / L.
[0018] Furthermore, in step S1, the concentration of the inorganic salt in the positive electrode electrolyte is 0.15-0.25 mol / L.
[0019] Furthermore, in step S1, the concentration of the inorganic salt in the positive electrode electrolyte is 0.2 mol / L.
[0020] Furthermore, in step S1, the concentration of ammonium chloride in the positive electrode electrolyte is 0.5-1.5 mol / L.
[0021] Further, in step S1, the concentration of ammonium chloride in the positive electrode electrolyte is 1 mol / L.
[0022] Furthermore, in step S1, the concentration of sulfuric acid in the positive electrode electrolyte is 0.05-0.15 mol / L.
[0023] Further, in step S1, the concentration of sulfuric acid in the positive electrode electrolyte is 0.1 mol / L.
[0024] Furthermore, in step S1 and step S2, ultrasound is performed for 2-4 minutes.
[0025] Furthermore, in step S1 and step S2, ultrasound is performed for 3 minutes.
[0026] The beneficial effect of adopting the above further solution is that the active substance in the solution is distributed more evenly.
[0027] Further, in step S1, argon gas is introduced for bubbling for 4-6 minutes.
[0028] Further, in step S1, argon gas is introduced for bubbling for 5 minutes.
[0029] The beneficial effect of adopting the above further solution is to remove the air remaining in the electrolyte solution.
[0030] Furthermore, in step S2, the volume of the negative electrode electrolyte is 5-15 mL.
[0031] Furthermore, in step S2, the volume of the negative electrode electrolyte is 10 mL.
[0032] Furthermore, in step S2, the concentration of the inorganic salt in the negative electrode electrolyte is 0.15-0.25 mol / L.
[0033] Further, in step S2, the concentration of the inorganic salt in the negative electrode electrolyte is 0.2 mol / L.
[0034] Further, in step S2, the concentration of ammonium chloride in the negative electrode electrolyte is 0.5-1.5 mol / L.
[0035] Further, in step S2, the concentration of ammonium chloride in the negative electrode electrolyte is 1 mol / L.
[0036] Further, in step S2, the concentration of sulfuric acid in the negative electrode electrolyte is 0.05-0.15 mol / L.
[0037] Furthermore, in step S2, the concentration of sulfuric acid in the negative electrode electrolyte is 0.1 mol / L.
[0038] Furthermore, in step S3, the specification of the ion membrane is: 3cm×3cm.
[0039] Furthermore, in step S3, the ion membrane is a perfluorosulfonic acid membrane.
[0040] The beneficial effects of adopting the above further solution are: improving the ion transmission efficiency, reducing the overall internal resistance of the battery after assembly, and avoiding unnecessary voltage loss.
[0041] Further, in step S3, the pretreatment includes the following steps: immersing the ion membrane in a hydrogen peroxide solution with a concentration of 4-6wt%, heating it in a water bath at 75-85°C for 0.5-1.5h, then immersing the ion membrane in a sulfuric acid solution with a concentration of 4-6wt%, heating it in a water bath at 75-85°C for 0.5-1.5h, and then washing away the residual acidic solution with deionized water.
[0042] Further, in step S3, the pretreatment includes the following steps: immersing the ion membrane in a 5wt% hydrogen peroxide solution, heating it in a water bath at 80°C for 1h, then immersing the ion membrane in a 5wt% sulfuric acid solution, heating it in a water bath at 80°C for 1h, and then washing away the residual acidic solution with deionized water.
[0043] Further, in step S4, the battery components include metal plates, rubber pads, conductive copper plates, carbon felt and graphite channels.
[0044] Furthermore, the specifications of the carbon felt are: 2 cm in length×2 cm in width×3 mm in thickness.
[0045] Further, in step S4, anhydrous ethanol is used for ultrasonication for 2-4 minutes.
[0046] Further, in step S4, anhydrous ethanol is used for ultrasonic treatment for 3 minutes.
[0047] The present invention has the following beneficial effects:
[0048] 1. The present invention selects the best performing molecule from a series of anthraquinone derivatives containing sodium sulfonate groups. The organic self-charging liquid flow battery based on quinone molecules provided by the present invention has the following characteristics: sodium anthraquinone sulfonate derivatives are used as the positive electrode material of the battery, and zinc and zinc ions, aluminum and aluminum ions, or magnesium and magnesium ions are used as negative electrode active materials. Anthraquinone derivatives have excellent electrochemical reversibility, high energy density and other characteristics. The sodium anthraquinone sulfonate molecules provide electrical energy depending on the gain and loss of electrons in the reversible reaction process of C=O and CO. When exposed to air, they can naturally self-charge; when air is involved, the positive electrode of the battery can be restored to the state before discharge. The present invention will broaden the application scope of zinc-organic aqueous batteries and provide an effective strategy for the development of self-charging energy storage devices.
[0049] 2. The organic self-charging liquid flow battery based on quinone molecules prepared by the method provided by the present invention increases a part of the battery capacity of the organic liquid flow battery itself, thereby increasing the energy density of the battery; and can be cycled for an ultra-long time with a good capacity retention rate.
[0050] 3. Oxygen is a low-cost resource that can be found everywhere in nature. Combining the chemical energy of oxygen with the electrochemical energy of electrode materials is an effective way to obtain a high-energy battery system. Using it to increase battery capacity is also an effective solution to the cost problem brought about by large-scale energy storage of liquid flow batteries.
[0051] 4. Anthraquinone derivatives containing carbonyl groups (C=O) and conjugated structures have excellent electrochemical reversibility and rapid reaction rates, making them undoubtedly good active materials for aqueous flow batteries. Among them, anthraquinone derivatives with sulfonic acid groups have become active electrode materials for acidic aqueous flow batteries by virtue of their good solubility in acidic aqueous solutions. However, their voltage is relatively low and they are usually used as negative electrode active materials for batteries. The present invention selects quinone and zinc for pairing and adjusts the battery voltage under acidic conditions. In addition, anthraquinone derivatives have carbon-oxygen double bonds (C=O) and reduced carbon-oxygen bonds (CO), which can be oxidized by oxygen to oxidize the carbon-oxygen single bonds to carbon-oxygen double bonds, allowing the positive electrode discharge products to return to their original state and achieve self-charging. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The graph shows the change of battery capacity and retention rate of organic self-rechargeable flow battery based on quinone molecules with the number of cycles;
[0053] Figure 2 The graph shows the change of open circuit voltage over time of organic self-charging flow batteries based on quinone molecules under different conditions;
[0054] Figure 3 The in-situ infrared test results of discharge products at different oxidation times;
[0055] Figure 4 The figure is the UV test result of discharge products under different oxidation time;
[0056] Figure 5 This is the zinc-based self-charging cycle performance diagram;
[0057] Figure 6 This is the magnesium-based self-charging cycle performance diagram;
[0058] Figure 7 This is the aluminum-based self-charging cycle performance diagram;
[0059] Figure 8 It is the relationship diagram between inflation time and theoretical capacity;
[0060] Fig. 9 This is a graph showing the internal resistance test results of an organic self-charging flow battery based on quinone molecules. DETAILED DESCRIPTION
[0061] The principles and features of the present invention are described below. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially. The ion membrane involved in the embodiments uses Dongyue perfluorosulfonic acid membrane.
[0062] Example 1
[0063] The preparation method of the organic self-charging liquid flow battery based on quinone molecules comprises the following steps:
[0064] S1. Add sodium anthraquinone-2,7-disulfonate, zinc trifluoromethanesulfonate, ammonium chloride and sulfuric acid into deionized water and stir evenly, then ultrasonicate for 3 minutes, and then introduce argon bubbling for 5 minutes to obtain 10 mL of positive electrode electrolyte, wherein the concentration of sodium anthraquinone-2,7-disulfonate in the positive electrode electrolyte is 0.1 mol / L, the concentration of zinc trifluoromethanesulfonate in the positive electrode electrolyte is 0.2 mol / L, the concentration of ammonium chloride in the positive electrode electrolyte is 1 mol / L, and the concentration of sulfuric acid in the positive electrode electrolyte is 0.1 mol / L;
[0065] S2, adding zinc trifluoromethanesulfonate, ammonium chloride and sulfuric acid to deionized water, stirring evenly, and then ultrasonicating for 3 minutes to obtain 10mL of negative electrode electrolyte, wherein the concentration of zinc trifluoromethanesulfonate in the positive electrode electrolyte is 0.2mol / L, the concentration of ammonium chloride in the positive electrode electrolyte is 1mol / L, and the concentration of sulfuric acid in the positive electrode electrolyte is 0.1mol / L;
[0066] S3, cutting the perfluorosulfonic acid membrane into 3cm×3cm, then immersing it in a 5wt% hydrogen peroxide solution, heating it in a water bath at 80°C for 1h, then immersing the ion membrane in a 5wt% sulfuric acid solution, heating it in a water bath at 80°C for 1h, and then washing away the residual acid solution with deionized water;
[0067] S4. The metal plates, rubber pads, conductive copper plates, carbon felt with specifications of 2 cm long × 2 cm wide × 3 mm thick, and graphite flow channels of each battery component are ultrasonically treated with anhydrous ethanol for 3 minutes, and then spliced in sequence. The positive and negative electrodes are then separated by a perfluorosulfonic acid membrane. The positive electrode electrolyte obtained in step S1 and the negative electrode electrolyte obtained in step S2 are pumped into the battery using a peristaltic pump, and then a resistance test is performed to obtain an organic self-charging liquid flow battery based on quinone molecules.
[0068] Example 2
[0069] The preparation method of the organic self-charging liquid flow battery based on quinone molecules comprises the following steps:
[0070] S1. Add sodium anthraquinone-2,7-disulfonate, aluminum chloride, ammonium chloride and sulfuric acid into deionized water and stir evenly, then ultrasonicate for 2 minutes, and then introduce argon bubbling for 4 minutes to obtain 10 mL of positive electrode electrolyte, wherein the concentration of sodium anthraquinone-2,7-disulfonate in the positive electrode electrolyte is 0.05 mol / L, the concentration of magnesium sulfate in the positive electrode electrolyte is 0.15 mol / L, the concentration of ammonium chloride in the positive electrode electrolyte is 0.5 mol / L, and the concentration of sulfuric acid in the positive electrode electrolyte is 0.05 mol / L;
[0071] S2. Add aluminum chloride, ammonium chloride and sulfuric acid into deionized water and stir evenly, then ultrasonicate for 2 minutes to obtain 10 mL of negative electrode electrolyte, wherein the concentration of magnesium sulfate in the positive electrode electrolyte is 0.15 mol / L, the concentration of ammonium chloride in the positive electrode electrolyte is 0.5 mol / L, and the concentration of sulfuric acid in the positive electrode electrolyte is 0.05 mol / L;
[0072] S3, cutting the perfluorosulfonic acid membrane into 3cm×3cm, then immersing it in a 4wt% hydrogen peroxide solution, heating it in a water bath at 75°C for 0.5h, then immersing the ion membrane in a 4wt% sulfuric acid solution, heating it in a water bath at 75°C for 0.5h, and then washing away the residual acid solution with deionized water;
[0073] S4. The metal plates, rubber pads, conductive copper plates, carbon felt with specifications of 2 cm long × 2 cm wide × 3 mm thick, and graphite flow channels of each battery component are ultrasonically treated with anhydrous ethanol for 2 minutes, and then spliced in sequence. The positive and negative electrodes are then separated by a perfluorosulfonic acid membrane. The positive electrode electrolyte obtained in step S1 and the negative electrode electrolyte obtained in step S2 are pumped into the battery using a peristaltic pump, and then a resistance test is performed to obtain an organic self-charging liquid flow battery based on quinone molecules.
[0074] Example 3
[0075] The preparation method of the organic self-charging liquid flow battery based on quinone molecules comprises the following steps:
[0076] S1. Add sodium anthraquinone-2,7-disulfonate, magnesium sulfate, ammonium chloride and sulfuric acid into deionized water and stir evenly, then ultrasonicate for 4 minutes, and then introduce argon bubbling for 6 minutes to obtain 10 mL of positive electrode electrolyte, wherein the concentration of sodium anthraquinone-2,7-disulfonate in the positive electrode electrolyte is 0.15 mol / L, the concentration of aluminum chloride in the positive electrode electrolyte is 0.25 mol / L, the concentration of ammonium chloride in the positive electrode electrolyte is 1.5 mol / L, and the concentration of sulfuric acid in the positive electrode electrolyte is 0.15 mol / L;
[0077] S2. Add magnesium sulfate, ammonium chloride and sulfuric acid into deionized water and stir evenly, then ultrasonicate for 4 minutes to obtain 10 mL of negative electrode electrolyte, wherein the concentration of aluminum chloride in the positive electrode electrolyte is 0.25 mol / L, the concentration of ammonium chloride in the positive electrode electrolyte is 1.5 mol / L, and the concentration of sulfuric acid in the positive electrode electrolyte is 0.15 mol / L;
[0078] S3, cutting the perfluorosulfonic acid membrane into 3cm×3cm, then immersing it in a 6wt% hydrogen peroxide solution, heating it in a water bath at 85°C for 1.5h, then immersing the ion membrane in a 6wt% sulfuric acid solution, heating it in a water bath at 85°C for 1.5h, and then washing away the residual acid solution with deionized water;
[0079] S4. The metal plates, rubber pads, conductive copper plates, carbon felt with specifications of 2 cm long × 2 cm wide × 3 mm thick, and graphite flow channels of each battery component are ultrasonically treated with anhydrous ethanol for 4 minutes, and then spliced in sequence. The positive and negative electrodes are then separated by a perfluorosulfonic acid membrane. The positive electrode electrolyte obtained in step S1 and the negative electrode electrolyte obtained in step S2 are pumped into the battery using a peristaltic pump, and then a resistance test is performed to obtain an organic self-charging liquid flow battery based on quinone molecules.
[0080] Test Example 1
[0081] The organic self-rechargeable liquid flow battery based on quinone molecules prepared in Example 1 was subjected to battery charge and discharge cycles. Figure 1 As shown. In the normal cycle battery (Open-cell), the electrolyte is driven by a pump to keep flowing during the entire cycle. In the static battery (Sealed-cell), the electrolyte is pumped into the flow battery before the cycle to fill the flow channel, and no flow circulation is required.
[0082] Depend on Figure 1 It can be seen that in the absence of air, the battery capacity is about 2 mAh, and after 1600 cycles, there is still nearly 100% retention rate.
[0083] Test Example 2
[0084] In situ infrared characterization shows that the electrical energy provided by the sodium anthraquinone sulfonate molecule depends on the gain and loss of electrons during the reversible reaction of C=O and CO. When exposed to air, it can naturally self-charge; when air is involved, the positive electrode of the battery can be restored to the state before discharge, and repeated 20 times, with a capacity of 100mAh. Obviously, the discharge capacity of the normal cycle battery is higher than that of the static battery, which may be related to the dissolved oxygen in the electrolyte. To verify this point of view, the open circuit voltage (OCV) test of the organic self-rechargeable liquid flow battery based on quinone molecules prepared in Example 1 was carried out to study the stability of the organic discharge products under different gas conditions. The results are as follows: Figure 2 shown.
[0085] Depend on Figure 2 It can be seen that the normal cycle battery is discharged to 0.01V, and then the aeration step is performed under different gas conditions. When the electrolyte is introduced into the pure O2 gas flow, the OCV of the battery rises rapidly and reaches the equilibrium voltage within 10 minutes; however, under Ar2 conditions, even if the aeration time exceeds 10 minutes, the OCV cannot reach the equilibrium voltage and basically remains unchanged at 0.82V. This result shows that the battery can operate stably in the absence of air and the organic molecular structure will not change.
[0086] Test Example 3
[0087] The results of Experimental Example 2 show that the battery discharge products can be oxidized by dissolved oxygen, and the oxidation rate depends on the oxygen concentration. To further explore, in-situ infrared testing was performed to deeply analyze the chemical redox process. The organic self-rechargeable liquid flow battery based on quinone molecules (2,7-ADQS︱︱Zn / Zn 2+ Liquid flow battery) at 20 mA cm -2 The electrolyte was discharged at a low current density of 0.01V, and then the fully discharged positive electrolyte was subjected to an oxygen bubbling experiment to react with oxygen. The in-situ infrared test results of the discharge products at different oxidation times are shown in Figure 2. Figure 3 shown.
[0088] Depend on Figure 3 It can be seen that with the change of bubbling time, 3200cm -1 , 1600cm -1 The absorption intensity on the left and right gradually increases, indicating that the C=O functional groups gradually increase, which means that the discharge products are gradually oxidized to a charged state during the whole process.
[0089] Test Example 4
[0090] The UV test results of the discharge products of the organic self-charging liquid flow battery based on quinone molecules prepared in Example 1 at different oxidation times are as follows: Figure 4 shown.
[0091] Depend on Figure 4 It can be seen that with the increase of oxidation time, the peak absorption intensity at 329nm wavelength gradually increases, and the peak absorption intensity at 388nm wavelength gradually decreases, which proves that the C=O functional group increases and the CO functional group decreases. After 8 minutes of oxidation, the discharge continues, and the UV absorption peak curve basically coincides with the UV absorption peak curve after the first discharge, which represents the excellent electrochemical reversibility of sodium anthraquinone-2,7-disulfonate.
[0092] In summary, the product after full discharge can spontaneously react with dissolved oxygen in the acidic electrolyte and return to the state before discharge (i.e., sodium anthraquinone-2,7-disulfonate), without the need for an external power source, directly increasing the battery capacity. This process is the chemical self-charging process. That is, in the acidic electrolyte (0.2M H2SO4+0.2M ZnOTF2), the discharge product of sodium anthraquinone-2,7-disulfonate couples with the zinc negative electrode to form a chemical self-charging battery.
[0093] Test Example 5
[0094] After 1 min of oxidation (i.e., chemical self-charging) of the organic self-rechargeable flow batteries based on quinone molecules prepared in Example 1, Example 2, and Example 3, the OCV and discharge capacity of the batteries are as follows: Figure 5-Figure 7 shown.
[0095] Depend on Figure 5 It can be seen that after 1 min of oxidation, the OCV of the self-rechargeable battery prepared in Example 1 recovered to 0.52 V at 40 mA cm -2 At the current density, the discharge capacity can reach 5 mAh. After repeated 1-min oxygenation (chemical self-charging) and discharge, the capacity retention rate remained basically unchanged after 20 cycles, and the cumulative capacity reached about 100 mAh, proving its stability.
[0096] Depend on Figure 6 It can be seen that after 1 min of oxidation, the OCV of the self-rechargeable battery prepared in Example 2 recovered to 0.5 V at 40 mA cm -2 At the current density, the discharge capacity can reach 5.5mAh. Repeated 1min oxygenation (chemical self-charging) and discharge, the capacity retention rate remains basically unchanged after 20 cycles, and the cumulative capacity reaches about 110mAh, proving its stability.
[0097] Depend on Figure 7 It can be seen that after 1 min of oxidation, the OCV of the self-rechargeable battery prepared in Example 3 recovered to 0.65 V at 40 mA cm -2 At the current density, the discharge capacity can reach 1.8 mAh. After repeated 1-min oxygenation (chemical self-charging) and discharge, the capacity retention rate remained basically unchanged after 20 cycles, and the cumulative capacity reached about 18 mAh, proving its stability.
[0098] Then the constant current discharge curves of the discharge battery after oxidation at different times were collected. The results are as follows: Figure 8 shown.
[0099] Depend on Figure 8It can be seen that the open circuit voltage of the self-charging liquid flow battery based on quinone molecules increases with the increase of oxidation time, and the discharge capacity is also improved. It can be seen from the figure that when the oxidation time is extended to 16 minutes, the ratio of its discharge capacity to the theoretical discharge capacity is close to 100%.
[0100] Test Example 6
[0101] The positive and negative electrodes of the organic self-rechargeable liquid flow battery based on quinone molecules prepared in Example 1 were connected to the Chenhua electrochemical workstation, the working electrode and the reference electrode were connected to the positive electrode, and the counter electrode was connected to the negative electrode. The internal resistance test was performed using the program AC impendence. The results are as follows: Fig. 9 shown.
[0102] Depend on Fig. 9 It can be seen that after the battery is assembled and tested by EIS, the internal resistance is basically normal and will not affect the experimental results.
[0103] In summary, the present invention successfully constructed a battery with anthraquinone-2,7-disulfonic acid sodium positive electrode and zinc negative electrode in an acidic electrolyte (i.e., 0.2M H2SO4+0.2M Zn(OTF)2). The results of the above test examples show that at 40mA cm -2 Under the conditions of 1,250 mAh, the specific capacity of the organic self-rechargeable flow battery (2,7-AQDS / / Zn) based on quinone molecules is 1250 mAh, with good cycle stability (100% after 1200 cycles), and good rate performance under O2-free conditions. The C=O group of sodium anthraquinone-2,7-disulfonate was identified as the redox active center by UV absorption and in situ Fourier transform infrared analysis, revealing a reversible C=O / CO charge storage mechanism. When the battery is opened to air, the positive electrode discharge products can be oxidized by dissolved oxygen in the electrolyte and restored to the initial state. Therefore, after the 2,7-AQDS / / Zn battery is exhausted, the chemical self-charging process can be achieved by exposing the battery to an air atmosphere. The battery can be quickly self-charged to 0.9 V. The chemical charge / constant current discharge process can be quickly and reversibly repeated 20 times.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. Organic self-charging flow battery based on quinone molecules, characterized in that: The positive electrode electrolyte of the organic self-charging flow battery based on quinone molecules includes sodium anthraquinone-2,7-disulfonate, an inorganic salt, ammonium chloride and sulfuric acid, and the negative electrode electrolyte of the organic self-charging flow battery based on quinone molecules includes an inorganic salt, ammonium chloride and sulfuric acid; The inorganic salt in the positive electrode electrolyte and the inorganic salt in the negative electrode electrolyte are both one of zinc trifluoromethanesulfonate, aluminum chloride and magnesium sulfate.
2. The method for preparing the organic self-charging liquid flow battery based on quinone molecules according to claim 1, characterized in that: The following steps are involved: S1. Add sodium anthraquinone-2,7-disulfonate, inorganic salt, ammonium chloride and sulfuric acid into deionized water and stir evenly, then perform ultrasonic treatment, and then perform ventilation bubbling treatment to obtain a positive electrode electrolyte; S2, adding inorganic salt, ammonium chloride and sulfuric acid into deionized water, stirring evenly, and then performing ultrasonic treatment to obtain a negative electrode electrolyte; S3, activating the ion membrane through pretreatment; S4. Ultrasound the components of the battery, and then assemble them in sequence. Then, the positive and negative electrodes are separated by an ion membrane. The positive electrode electrolyte obtained in step S1 and the negative electrode electrolyte obtained in step S2 are pumped into the battery by a peristaltic pump. Then, a resistance test is performed to obtain an organic self-charging liquid flow battery based on quinone molecules.
3. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S1, the concentration of the anthraquinone-2,7-disulfonic acid sodium in the positive electrode electrolyte is 0.05-0.15 mol / L, the concentration of the inorganic salt in the positive electrode electrolyte is 0.15-0.25 mol / L, the concentration of the ammonium chloride in the positive electrode electrolyte is 0.5-1.5 mol / L, and the concentration of the sulfuric acid in the positive electrode electrolyte is 0.05-0.15 mol / L.
4. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S1 and step S2, ultrasonication is performed for 2-4 minutes.
5. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S1, argon gas is introduced for bubbling for 4-6 minutes.
6. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S2, the concentration of the inorganic salt in the negative electrode electrolyte is 0.15-0.25 mol / L, the concentration of ammonium chloride in the negative electrode electrolyte is 0.5-1.5 mol / L, and the concentration of sulfuric acid in the negative electrode electrolyte is 0.05-0.15 mol / L.
7. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S3, the ion membrane is a perfluorosulfonic acid membrane.
8. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S3, the pretreatment includes the following steps: immersing the ion membrane in a hydrogen peroxide solution with a concentration of 4-6wt%, heating it in a water bath at 75-85°C for 0.5-1.5h, then immersing the ion membrane in a sulfuric acid solution with a concentration of 4-6wt%, heating it in a water bath at 75-85°C for 0.5-1.5h, and then washing away the residual acidic solution with deionized water.
9. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S4, the battery components include a metal plate, a rubber pad, a conductive copper plate and a graphite flow channel.
10. The method for preparing an organic self-charging liquid flow battery based on quinone molecules according to claim 2, characterized in that: In step S4, anhydrous ethanol is used for ultrasonication for 2-4 minutes.
Citation Information
Patent Citations
Quinone metal redox couple flow cell system
CN106532093A
Organic system lithium-quinone flow battery
CN106549179A
Electrolyte additives for zinc metal electrodes
CN110770949A
Self-charging electrochemical cell
CN117751475A
Redox flow battery and redox flow battery system
JP2017050201A